Microeconomics: Principles, Problems, and Policies - Campbell R. McConnell; Stanley L. Brue (Boston: Irwin/McGraw-Hill, 1998)
Welcome to the fourteenth edition of "Macroeconomics" (and its companion editions of "Economics" and "Microeconomics"), the nation's best-selling economics texts. It has been adapted into Canadian, Australian, Italian, and Russian editions and translated into French, Spanish, and several other languages.
(NP(B/16933-(NP(B/16934s
+CD
+Photos
Keywords: banking -- international economics -- world economy -- countries